A Review on Validation of Jamun Seed Powder in Diabetic Mellitus - Sahani, N.F.; Maheez, M.C.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels and remains a global health concern. Among various plant-based interventions explored for glycemic control, Syzygium cumini (commonly known as Jamun) has gained attention for its antidiabetic properties. This review highlights the therapeutic potential of different parts of Syzygium cumini, particularly the seed powder, in the management of diabetes. Bioactive compounds such as jamboline, ellagic acid, and flavonoids present in Jamun seeds contribute to hypoglycemic effects through multiple mechanisms, including enhanced insulin secretion, improved insulin sensitivity, and inhibition of carbohydrate-digesting enzymes. Several in vitro, animal, and limited clinical studies have demonstrated reductions in fasting blood glucose, HbA1c, and serum lipid levels with Jamun seed supplementation. Furthermore, Jamun may offer adjunct benefits in controlling diabetic complications through its antioxidant and lipid-lowering effects. This review synthesizes current evidence on the efficacy and mechanisms of Syzygium cumini in diabetes management and underscores its potential as a complementary therapeutic agent.
Keywords: Syzygium cumini; Jamun; Diabetes; Hypoglycemia; Blood glucose